Fundamentals of Kalman filtering : a practical approach - Zarchan, Paul; Musoff, Howard (American Institute of Aeronautics and Astronautics, Inc., 2015)
This is a practical guide to building Kalman filters that shows how the filtering equations can be applied to real-life problems. Numerous examples are presented in detail, showing the many ways in which Kalman filters can be designed. Source code listings appearing in the text have been converted from FORTRAN to MATLAB(R). In certain instances, the authors intentionally introduce mistakes to the initial filter designs to show the reader what happens when the filter is not working properly. The book carefully sets up a problem before the Kalman filter is actually formulated, to give the reader an intuitive feel for the problem being addressed. The authors illustrate different filtering approaches. Readers will gain experience in software and performance tradeoffs for determining the best filtering approach. -- Edited summary from book.
Keywords: Kalman filtering.; Control theory.; Aeronautics -- Statistical methods.; elektronické knihy; electronic books